Correction: A prospective cohort study of dynamic cell-free DNA elevation during cardiac surgery with cardiopulmonary bypass. - Shlomo Yaron Ishay; Muhammad Abu-Tailakh; Lior Raichel; Tal F Hershenhoren; Menahem Matsa; Oren Lev-Ran; Sahar Gideon; Amos Douvdevani (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0276443.].